A Conserved Arginine-containing Motif Crucial for the Assembly and Enzymatic Activity of the Mixed Lineage Leukemia Protein-1 Core Complex - Patel, Anamika; Vought, Valarie E.; Dharmarajan, Venkatasubramanian; Cosgrove, Michael S. (The Journal of biological chemistry, 2008)
The mixed lineage leukemia protein-1 (MLL1) belongs to the SET1 family of histone H3 lysine 4 methyltransferases. Recent studies indicate that the catalytic subunits of SET1 family members are regulated by interaction with a conserved core group of proteins that include the WD repeat protein-5 (WDR5), retinoblastoma-binding protein-5 (RbBP5), and the absent small homeotic-2-like protein (Ash2L). It has been suggested that WDR5 functions to bridge the interactions between the catalytic and regulatory subunits of SET1 family complexes. However, the molecular details of these interactions are unknown. To gain insight into the interactions among these proteins, we have determined the biophysical basis for the interaction between the human WDR5 and MLL1. Our studies reveal that WDR5 preferentially recognizes a previously unidentified and conserved arginine-containing motif, called the “Win” or WDR5 interaction motif, which is located in the N-SET region of MLL1 and other SET1 family members. Surprisingly, our structural and functional studies show that WDR5 recognizes arginine 3765 of the MLL1 Win motif using the same arginine binding pocket on WDR5 that was previously shown to bind histone H3. We demonstrate that WDR5's recognition of arginine 3765 of MLL1 is essential for the assembly and enzymatic activity of the MLL1 core complex in vitro.